1968
DOI: 10.1139/p68-347
|View full text |Cite
|
Sign up to set email alerts
|

The 1966–67 increase in solar cosmic-ray activity

Abstract: A significant increase in solar cosmic-ray activity began in early 1966. During the period from March 1966 to June 1967, 14 events were observed. This can be compared to one event in 1964 and one event in 1965. Events in 1966 occurred on 24 March, 7 July, 28 August, 2 September, and 14 September. Events in 1967 include those of 28 January, 2 February, 7 February, 13 February, 11 March, 23 March, 23 May, 28 May, and 6 June.The 2 September 1966 event, reaching a maximum of 13 dB (~105/cm2 s > 2 MeV), was the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

1969
1969
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 2 publications
0
15
0
Order By: Relevance
“…See Table L For the years prior to 1957.5 we have assembled a partial list of major He flares in regions with very small or no spots. The list includes the flares reported by Richardson (1944) andNewton (1935), and also all flares of importance ~2 for which Ziirich and Mount Wilson spot data confirmed remarks in the Quarterly Bulletin, either those by the editor, "Aucune tache n'a 6t6 observ6e/t Meudon dans ce centre", or those by individual reporters "Pas de taches visibles dans les alentours." Mme.…”
Section: The Present Surveymentioning
confidence: 99%
See 1 more Smart Citation
“…See Table L For the years prior to 1957.5 we have assembled a partial list of major He flares in regions with very small or no spots. The list includes the flares reported by Richardson (1944) andNewton (1935), and also all flares of importance ~2 for which Ziirich and Mount Wilson spot data confirmed remarks in the Quarterly Bulletin, either those by the editor, "Aucune tache n'a 6t6 observ6e/t Meudon dans ce centre", or those by individual reporters "Pas de taches visibles dans les alentours." Mme.…”
Section: The Present Surveymentioning
confidence: 99%
“…A small number of exceptions to this statement may have occurred. Polar cap absorption, albeit small, was recorded in appropriate time association with the flare on 1967 February 13d17h47 m (Masley and Goedeke, 1968). Malitson (1963) lists a small PCA on September 2, 1959 in the hours following flare No.…”
Section: Particle Effects Of Major H~ Flares In Regions With Small Ormentioning
confidence: 99%
“…A comparison of the data from this event with riometer data (MASLEY, 1966) has shown that the total counting rate of the OGO detector is 6 to 8 times higher than if the anti-coincidence were working. Since protons of less than 16 MeV are constrained to enter the crystal through the detector opening, it is only the protons of greater energy that will cause the main difficulties.…”
Section: I/t (Hrs) -Imentioning
confidence: 85%
“…In any case the PCA confirms the small importance of the particle event. Open circles show experimental data obtained from satellites by Bostrom (Masley and Goedeke, 1967), McCracken et al (1967 and Kinsey and McDonald (1968). On September 2 dots represent maximum flux values obtained by Durgaprasad et al (1968) during three sounding-rocket flights.…”
Section: E Polar Cap Absorptionmentioning
confidence: 93%